2020
DOI: 10.1038/s41598-020-66295-0
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation even after injury ameliorates cisplatin-induced nephropathy via reducing macrophage infiltration

Abstract: The efficacy of prior activation of an anti-inflammatory pathway called the cholinergic antiinflammatory pathway (CAP) through vagus nerve stimulation (VNS) has been reported in renal ischemia-reperfusion injury models. However, there have been no reports that have demonstrated the effectiveness of VNS after injury. We investigated the renoprotective effect of VNS in a cisplatin-induced nephropathy model. C57BL/6 mice were injected with cisplatin, and VNS was conducted 24 hours later. Kidney function, histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
3
10
0
Order By: Relevance
“…The results confirmed that VNS had an organ-protective effect, even post-cisplatin-induced nephropathy, and that CCL2 and CCL11, factors related to immune cell chemotaxis, were suppressed in macrophages through α7nAChR (Fig. 3f) [15].…”
Section: Vns and Acute Kidney Injury (Aki)supporting
confidence: 70%
“…The results confirmed that VNS had an organ-protective effect, even post-cisplatin-induced nephropathy, and that CCL2 and CCL11, factors related to immune cell chemotaxis, were suppressed in macrophages through α7nAChR (Fig. 3f) [15].…”
Section: Vns and Acute Kidney Injury (Aki)supporting
confidence: 70%
“…Therefore, activation of vagal efferent signaling by VNS results in activation of the sympathetic innervation and release of norepinephrine (NE) in the spleen. Accordingly, splenectomy reverses VNS protective effects in models of endotoxemia ( Huston et al., 2006 ), nephropathy ( Uni et al., 2020 ), kidney ischemia-reperfusion injury ( Inoue et al., 2016 ) and colitis ( Ji et al., 2014 ) ( Fig. 1 a).…”
Section: Vagus Nerve and Cholinergic Immunomodulationmentioning
confidence: 91%
“…From a clinical perspective, this study suggested that VNS could be employed prophylactically in situations in which the patient is at high risk of developing AKI. This was followed by a study demonstrating that VNS administered 24 h after cisplatin treatment was protective against kidney injury which was dependent upon the CAP [ 86 ]. Preclinical studies have clearly demonstrated a protective role of VNS in kidney injury and clinical trials are now warranted to determine its therapeutic benefit in patients.…”
Section: Potential Uses and Mechanisms Of Vnsmentioning
confidence: 99%